Pengembangan Media Digital Pop-Up Book pada Materi Ekosistem untuk Meningkatkan Hasil Belajar Siswa Kelas 5 SD Negeri Harjosari 01 - Mutea Septiana Mutiara; Nyoto Hardjono (Journal on Education, 2023)
This study aims to 1) produce Digital Pop-up book learning media. 2) know the validator's response to the developed media. 3) knowing the response of students and educators to the media developed. 4) knowing the influence of developing Digital Pop-Up Book learning media to improve the learning outcomes of grade 5 students of SD Negeri Harjosari 01 on Ecosystem material. Making learning media using the RnD (Research and Development) method by adapting the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Analysis of experimental data used One Group Pretest-Posttest design, students' pretest and posttest learning outcomes were tested using paired sample t-test. The results of the validation test of media experts obtained scores with a percentage of 85%, material experts 88% and linguists 84% with very good criteria. The results of the teacher response validation test obtained a feasibility score of 94% and student responses of 85% with very good criteria, so that the Digital Pop-Up Book learning media is effective and suitable for use in classroom learning. The paired sample t-test results are known that the value of Sig. (2-tailed) pretest learning outcomes and postest learning outcomes is 0.000 < 0.05, then the results of the H0 research hypothesis are rejected and the Ha research hypothesis is accepted, so it can be concluded that there is a significant development influence between digital learning media Digital Pop-Up Book to improve the learning outcomes of grade 5 students of SD Negeri Harjosari 01 on Ecosystem material.